Isolation and characterization of the RNA2+, RNA4+, and RNA11+ genes of Saccharomyces cerevisiae. - Soltyk, A (1984)
We used genetic complementation to isolate DNA fragments that encode the Saccharomyces cerevisiae genes RNA2+, RNA4+, and RNA11+ and to localize the genes on the cloned DNA fragments. RNA blot-hybridization analyses coupled with genetic analyses indicated the RNA2+ is coded by a 3.0-kilobase (kb) transcript, RNA4+ is coded by a 1.6-kb transcript, and RNA11+ is coded by a 1.3-kb or a 1.7-kb transcript or both; none of the cloned genes contains detectable introns. All three genes were transcribed into messages of very low abundance (approximately 20 times lower than a ribosomal protein message). DNA blot-hybridization revealed that all cloned genes are represented only once in the yeast chromosome. mRNA for RNA2+ and RNA4+ is produced in approximate proportion to gene dosage, whereas RNA11+ transcription appears to be not nearly so dependent on gene dosage. On a medium-copy plasmid (5 to 10 copies per cell), each cloned gene complemented mutations only in its own gene, indicating that each gene encodes a unique function. Genetic analysis by integrative transformation indicated that we cloned the RNA2+, RNA4+, and RNA11+ structural genes and not second-site suppressors.